Modifications of the SURDAT database of the physicochemical properties of metals and alloys (Journal of Mining and Metallurgy, Section B: Metallurgy, 2012)
Experimental studies of the surface tension and the density were carried out by means of the maximum bubble pressure method and the dilatometric technique and next, they were compiled with the results of over 12 years of research of the liquid pure components, binary and multicomponent alloys, with the aim to create the SURDAT database of the Pb-free soldering materials. In the last years, a modification of SURDAT has been conducted. The new version, beside the earlier data of the physical properties, also contains such data as: the viscosity data, selected data of the mechanical and electrical properties, the DTA data and the meniscographic study results (contact angle, wetting time, wetting force and interfacial tension). Additionally, the data base of the heat properties, worked out at NIST (National Institute of Standard and Technology from Boulder in Colorado) has been implemented.